Optimisation of cryovials and milt dilution ratios to upscale carp sperm cryopreservation for use in hatchery seed production: Upscaling of Carp Sperm Cryopreservation - Kumar, Santosh; Kumar, Aditya; Rama Shankar Sah; Ajay Kumar Singh; Ajay Yadav; Arvind Verma; Deepti Negi; Hayin Tamut; Kuldeep Kumar Lal (Indian Journal of Fisheries, 2023)
This study reports the experimental results carried out to optimise containers and milt dilution ratios for carp sperm cryopreservation, in order to make the process simple and compatible with the needs of commercial carp seed production, which is a small-scale and low technology sector in Asia. The procedure optimisation for up-scaling was assessed by the ability of cryopreserved sperms to fertilise Cyprinsu carpio eggs and hatching percentage, in three different experiments. In the first experiment, we tested the effect of milt to different extender dilutions (1:4, 1:6 and 1:8); the second experiment tested the effect of container capacities (0.5 ml French straw; 2 ml and 5 ml cryovials) with two dilution ratios (1:3 and 1:6) and in the third experiment, the efficacy of pre-mix of extender salts and individually pre-weighed salts stored over 5 months was compared with fresh preparation of extender. Out of the three dilutions tested, two dilutions viz., 1:4 and 1:6, yielded hatching above 50%. We also used the milt cryopreserved at dilution of 1:3 which was post-thaw diluted with extender, to make final dilution of 1:6, to fertilise the eggs. This post-thaw dilution in the ratio 1:6, yielded the results comparable to the milt cryopreserved in 1:6 dilution. This approach can help small-scale seed producers to store more sperm within the limits of the cost of liquid nitrogen. The extender salt composition, pre-weighed and pre-mixed, was also found to give comparable results to the fresh composition after storage over 5 months. This can assist in developing ready to use, cost-effective, working kits available to semi-technical hatchery seed producers. The parameters optimised in the study has potential to be transformed as an easy strategy with the use of 5 ml vial, cryopreserved at 1:3 dilution, with further post-thaw dilution at site, thus aiding in fertilisation of large volume of eggs produced by high fecund carp species within the limited time available for maintaining good gamete quality. Keywords: Cryobanking, Cryovials, Dilution, Salt premix